Parent-Mediated Interventions for Children and Adolescents With Autism Spectrum Disorders: A Systematic Review and Meta-Analysis - Conrad, Charlotte Engberg; Rimestad, Marie Louise; Rohde, Jeanett Friis; Petersen, Birgitte Holm; Korfitsen, Christoffer Bruun; Tarp, Simon; Cantio, Cathriona; Lauritsen, Marlene Briciet; Händel, Mina Nicole (Frontiers in Psychiatry, 2021)
There has been increasing interest in parent-mediated interventions (PMIs) for children with autism spectrum disorders (ASDs). The objective of this systematic review and meta-analysis was to examine the effect of PMIs compared to no PMI for children with ASD aged 2-17 years. The primary outcome was adaptive functioning rated by a parent or clinician. The secondary outcomes were long-term adaptive functioning rated by the parents, adverse events, core symptoms of ASD, disruptive behavior, parental wellbeing, quality of life of the child rated by the parents and anxiety. The MEDLINE, PsycInfo, Embase and CINAHL databases were searched in March 2020. The Cochrane Risk of Bias Tool was used to rate the individual studies, and the certainty in the evidence was evaluated using GRADE. We identified 30 relevant randomized controlled trials (RCTs), including 1,934 participants. A clinically relevant effect of PMIs on parent-rated adaptive functioning was found with a low certainty of evidence (Standard mean difference (SMD): 0.28 [95% CI: -0.01, 0.57] on Vineland Adaptive Behavior Scales (VABS), whereas no clinically relevant effect was seen for clinician-rated functional level, with a very low certainty of evidence (SMD on Clinical Global Impressions (CGI)-severity scale: SMD -0.45 [95% CI: -0.87, -0.03]). PMIs may slightly improve clinician-rated autism core symptoms (SMD: -0.35 [95% CI: -0.71, 0.02]). Additionally, no effect of PMIs on parent-rated core symptoms of ASD, parental well-being or adverse effects was identified, all with a low certainty of evidence. There was a moderate certainty of evidence for a clinically relevant effect on disruptive behavior (SMD: 0.55 [95% Cl: 0.36, 0.74]). The certainty in the evidence was downgraded due to serious risk of bias, lack of blinding, and serious risk of imprecision due to few participants included in meta-analyses. The present findings suggest that clinicians may consider introducing PMIs to children with ASD, but more high-quality RCTs are needed because the effects are not well established, and the results are likely to change with future studies. The protocol for the systematic review is registered at the Danish Health Authority website (www.sst.dk).